LEADERSHIP OF VILLAGE KYAI IN THE INFLUENCE OF RELIGIOUS MODERATION - Sarkowi, Sarkowi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This  research  is  descriptive  qualitative  in  nature  with  a  phenomenological approach in analyzing the  leadership of  village Kiai in efforts to mainstream religious moderation for the abangan in Songon, Pondok Joyo, Semboro Jember, East Java. The results  of this research  show that the  leadership  authority of village  Kiai in the  global era  has  not  been  shifted,  continues  to  exist,  and  is  the  main  reference  in  providing example,  da'wah,  education  and  consultation  in  building  the  foundation  for mainstreaming  religious  moderation.  In  implementing  his  leadership,  he  uses  a situational  approach  based  on  religious  ethics,  through  various  activities  that  are routine  and  conditional,  daily,  weekly,  monthly  and  yearly,  taking  into  account  the context  and  culture  of  the  Songon  community.  In  leading  various  religious  and  non- religious  activities,  he  always  instills  values,  develops  attitudes  and  thoughts  that  are moderate,  tolerant  and  peaceful  as  well  as  love  for  the  Indonesian  homeland  by referring  to  the  concepts  that  have  been  taught  or  embraced  by  the  NU  organization through educational, religious and cultural activities.